Synthesis, structure analysis, and optical parameters investigation of Zirconium dioxide nanoparticles pure and dispersed in poly(vinylpyrrolidone) nanocomposite - Abdulhakim A. Jangher; Abdullah H. Almokhter; Ali Ben Ahmed (The Libyan Journal of Science, 2024)
Poly(vinylpyrrolidone), PVP is used in several potential applications, based on its particular chemical and physical properties. The objective of this work is to prepare PVP-zirconium dioxide, (PVP-ZrO2) nanocomposites. ZrO2 NPs were obtained by the sol-gel method. The formation of spherical ZrO2 NPs, PVP film, and PVP-ZrO2 nanocomposites was characterized using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and optical spectroscopy (UV-visible and Fluorescence). The XRD patterns revealed the monoclinic crystal structure of the ZrO2 NPs (average size of 19 nm) and the successful doping operation. The FT-IR spectra revealed the strong interaction between the PVP polymer and the ZrO2. The absorption edges of all nanocomposites shifted to the higher wavelength region compared to the pure polymer. The results indicate that the optical bandgap values decreased as the ZrO2 content increased. Additionally, from pure PVP to nanocomposites by different concentrations, the emission peak broadens towards the higher wavelength side, with offset superiority for 5% ZrO2 NPs/PVP nanocomposite. All these results indicate the eligibility of the ZrO2NPs/PVP blend nanocomposites for different optoelectronic applications.